2017
DOI: 10.1037/fam0000293
|View full text |Cite
|
Sign up to set email alerts
|

Graphic methods for interpreting longitudinal dyadic patterns from repeated-measures actor–partner interdependence models.

Abstract: Researchers commonly use repeated-measures actor-partner interdependence models (RM-APIM) to understand how romantic partners change in relation to one another over time. However, traditional interpretations of the results of these models do not fully or correctly capture the dyadic temporal patterns estimated in RM-APIM. Interpretation of results from these models largely focuses on the meaning of single-parameter estimates in isolation from all the others. However, considering individual coefficients separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…For mothers, the actor RSA effect was statistically significant and positive. Because the value of this effect was positive but less than 1, this actor RSA effect reflects regression to the mean (e.g., Perry et al, ), in which epochs marked by high RSA tend to be followed by lower RSA epochs, while low RSA epochs tend to be followed by higher RSA epochs, centered around the individual's mean level of RSA. Maternal depressive symptoms moderated the actor RSA effect for mothers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For mothers, the actor RSA effect was statistically significant and positive. Because the value of this effect was positive but less than 1, this actor RSA effect reflects regression to the mean (e.g., Perry et al, ), in which epochs marked by high RSA tend to be followed by lower RSA epochs, while low RSA epochs tend to be followed by higher RSA epochs, centered around the individual's mean level of RSA. Maternal depressive symptoms moderated the actor RSA effect for mothers.…”
Section: Resultsmentioning
confidence: 99%
“…Broadly, high levels of RSA during one epoch predicted continued high levels of RSA in the subsequent epoch for both mothers and youth throughout the discussion tasks. The magnitude of the actor effects (positive, but less than 1) also indicates a “regression to the mean” effect (Perry et al, ), such that elevated RSA in one epoch predicted subsequent RSA that was elevated, but closer to the mean (while low RSA in one epoch predicted subsequent RSA levels that were low, but closer to the mean).…”
Section: Discussionmentioning
confidence: 99%
“…Probing of this interaction revealed that at low levels of accommodation, there was a positive actor effect for the partner. Because this actor effect is closer to a value of 1.0, it indicates that partners’ arousal is more stable over time when accommodation was lower relative to when accommodation was higher (Perry et al., ).…”
Section: Resultsmentioning
confidence: 98%
“…In the context of psychotherapy, this model is sometimes termed a repeated measures (RM) APIM (cf. Baucom, Dickenson, et al, 2015;Crowell et al, 2014;Perry et al, 2017). Extending the model to further include additional occasions allows testing whether the actor and partner effects can explain the longitudinal interrelations -i.e., whether the processes are interdependent over time (Laurenceau & Bolger, 2005).…”
Section: Insert Figure 1 Herementioning
confidence: 99%
“…But such a constraint can be relaxed in order to account for potential influences of lags greater than one or to test for differences in the parameters across various segments in the data. As noted previously, if an APIM is applied to more than two measures, and the actor and partner influences are constrained to be equal over time, the resulting RM-APIM is equivalent to the auto-regressive model described here (Nestler et al, 2015;Perry et al, 2017). AR models allow answering questions pertinent to dyadic interactions.…”
Section: Insert Figure 4 Herementioning
confidence: 99%